(3QSGdI SHH GdCSHGHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe HSe Gddg GdQMef GdQMje hGdMeO dehdGfG GdPi djS dg ai GdSeGA fXjQ hdG ai GdCQV hgh Hg NHjQ s
(3BNQgG (B:s
(3dCf Gdjejf hGdTeGd eVdJGf hGdhSWi gi GdWQjb Edi GdfLGI hGdhUhd Edi ZGjI GdZGjGJ hfgGjI GdfgGjGJ hgj YHGOI ehdGfG Ld PcQg hJhMjOg SHMGfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds